Floquet Weyl nodes in Weyl semimetal via a one-photon resonance. (21st November 2017) - Cao, Jie; Qi, Fenghua; Xiang, Yuanyuan
Abstract: Topological phase transition under the influence of periodic driving is regarded as one of the major topics in materials science. For most materials, we usually expect a full dynamical gap opened at the resonance energy, which can convert a topologically trivial state into a Floquet topological insulator state. However, according to both analytical and numerical calculations, we find that new Weyl nodes emerge on the resonance sphere when a Weyl semimetal is irradiated by any kind of continuous driving. These nodes are called Floquet Weyl nodes due to linear dispersion around them. In general cases, we can find four Floquet Weyl nodes, which have the same chiralities with the equilibrium Weyl node.